Knowing what you know about your faith an interactive application for measuring your faith in Islam - Gharamah, Abdulrahman; Noordin, Mohamad Fauzan; Imtiaz Ali, Najma; Brohi, Imtiaz Ali; Akram, M. Zeki (Institute of Electrical and Electronics Engineers Inc., 2018)
The My Faith web (MYF-web) application is an interactive system designed to help an ordinary Muslim to become a better Muslim. The initial motivation for the system is to comply with Qur’an and Sunnah where Muslims are always urged to be better ones and work for the next lives or the afterlives and considering the current lives and do the most that can be to satisfy both lives. The system composed of many components that vary from explaining Islamic concepts to private interactive arguments between the user and the system. The main component or the heart of the system, however, is the Islamic Aspects which consists of three parts: Aqeedah, Akhlaq and Sharia’h. The objective of the system is to enable an individual to do self-assessment for him/her self in order to measure his/her believes and practices in light of Islamic teachings. In addition, the application motivates knowledge worker in Islamic studies to contribute with their knowledge through knowledge sharing with the application. Knowledge management, the processer and intelligent engine, is another major component of the system. This propagation of Islamic knowledge through applications will lead the Muslim Ummah to shape a better interrelated Muslim society for the future.